2016
DOI: 10.1002/alr.21782
|View full text |Cite
|
Sign up to set email alerts
|

Non-diluted seawater enhances nasal ciliary beat frequency and wound repair speed compared to diluted seawater and normal saline

Abstract: BackgroundThe regulation of mucociliary clearance is a key part of the defense mechanisms developed by the airway epithelium. If a high aggregate quality of evidence shows the clinical effectiveness of nasal irrigation, there is a lack of studies showing the intrinsic role of the different irrigation solutions allowing such results. This study investigated the impact of solutions with different pH and ionic compositions, eg, normal saline, non‐diluted seawater and diluted seawater, on nasal mucosa functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
23
0
5
Order By: Relevance
“…In 2016, an in‐vitro study by Bonnomet et al showed nondilute IS seawater solution more effectively improved ciliary beat frequency and wound repair speed when compared with dilute IS seawater and regular IS (Table ) . In addition, regular IS had a negative effect on epithelial cell function . A 2015 study by Woods et al compared the effect of low‐salt solution, IS, and HS on the antimicrobial activity of nasal secretions (Table ) .…”
Section: Nasal Saline Compositionmentioning
confidence: 99%
“…In 2016, an in‐vitro study by Bonnomet et al showed nondilute IS seawater solution more effectively improved ciliary beat frequency and wound repair speed when compared with dilute IS seawater and regular IS (Table ) . In addition, regular IS had a negative effect on epithelial cell function . A 2015 study by Woods et al compared the effect of low‐salt solution, IS, and HS on the antimicrobial activity of nasal secretions (Table ) .…”
Section: Nasal Saline Compositionmentioning
confidence: 99%
“…Saline solution used as nasal wash with large volume-low pressure delivery devices or as multiple irrigations is still considered one of the best and safest treatments to ease CRS symptoms as these treatments are safe and have a positive benefit/risk ratio [25,26]. The mode of action, beyond the flushing mechanical action of saline solutions is not clearly established but regular nasal washes may help clean nasal passage, improve respiration, ciliary beats or reduce microbial load thereby alleviating CRS symptoms [27].…”
Section: Discussionmentioning
confidence: 99%
“…The salt concentration cannot be increased above 3.4%, as the solution then becomes too irritable to the nasal mucosa and may cause severe inflammation and nasal mucosa damage. A few solutions containing higher salt concentrations such as pure or diluted sea water exist on the market as symptomatic treatments only [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В рандомизированном слепом исследовании in vitro сравнили влияние изотонического (0,9%) раствора хлорида натрия, 30% раствора морской воды и натуральной неразбавленной морской воды на частоту биения ресничек респираторного эпителия. Растворы морской воды, особенно неразбавленной, существенно увеличивали частоту биения ресничек по сравнению с изотоническим (0,9%) раствором хлорида натрия, а также ускоряли заживление поврежденного эпителия [41].…”
unclassified